Left ventricular assist devices—current state and perspectives - Prinzing, Anatol; Herold, Ulf; Berkefeld, Anna; Krane, Markus; Lange, Rüdiger; Voss, Bernhard (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Mechanical circulatory support devices have become an important treatment tool for severe acute and chronic heart failure, since heart transplantation cannot meet the demands because of a lack of available donor organs. Since implantation of the first ventricular assist device a constant development of the suitability of these devices has been made. This review will introduce different generations of left ventricular assist devices (LVAD) and elaborate on clinical indications, risk stratification and current literature.